A Community-Based Heart Health Intervention: Culture-Centered Study of Low-Income Malays and Heart Health Practices - Kaur-Gill, Satveer; Dutta, Mohan Jyoti; Bashir, Munirah Binte (Frontiers in Communication, 2020)
This paper reports the formative research findings of a culture-centered heart health intervention with Malay community members belonging to low-income households. The community-based culture-centered intervention entailed working in the grassroots with community stakeholders to tailor a heart health campaign with and for low-income Malay Singaporeans. Community stakeholders designed and developed the heart health communicative infrastructures during six focus group sessions detailed in the results. The intervention included building smoking cessation information accessible to the community, the curation of heart healthy Malay centric recipes, and developing culturally responsive information infrastructures to understand a myocardial infarction. The intervention sought to bridge the gap for the community where there is an absence of culturally-centered communicative infrastructures on heart health.